Pilot study of laboratory safety status for laboratory workers Troubleshooting of efect formation in injection-moulded thermoplastic tensile specimens by optical microscopy technique - Kreunin, Paweena; Ketkoom, Natthakarn; Kongwithtaya, Sombat (Bulletin of Applied Sciences, 2014)
This pilot study is an exploratory research. The focus group of the study was laboratory workers who received the training of laboratory safety and other laboratories related courses from the Bureau of Laboratory Personnel Development, Department of Science Service, Thailand during 2010-2014. The questionnaire was designed to collect the data of safety practices and opinions within their own laboratory settings. Questionnaires was collected and analyzed. The results showed that the subjects of the study were coming from diversified groups, i.e. testing, calibration, R&D, and academic laboratories which were the focused group of the pilot study. The results showed that more than 50% of the workers were received inadequate training relating to the safety work practices. The majority of the people showed frequent of lone working, and inappropriate use of Safety Data Sheet (SDS) and Personal Protective Equipment (PPE). About 87.1% of workers reported accidents in the laboratories, and the two most important factors to cause accidents were related to humans i.e. the unawareness of workers who were involved in laboratory work and the inadequate of knowledge about safety of laboratory workers. Moreover, most subjects reported that their own laboratories setting were not safe in term of physical safety management or did not have the routine risk assessment of the laboratory. The majority of them believe that their laboratory safety management should be improved and they should receive training in many areas of laboratory safety. The results can be used in the training courses and present to the public to raise awareness of safe work practice.